Revealing the therapeutic potential of teriparatide: a review - Srivastava, Sushant; Kumar, Arvind; Kundnani, Vishal; Ajgaonkar, Amit (International Journal of Research in Orthopaedics, 2024)
Teriparatide is an FDA-approved medication for osteoporosis that presents promising results in treating various musculoskeletal conditions. It helps in improving the bone mineral density and preventing fractures in individuals with osteoporosis. Its effectiveness in treating non-union and delayed union fractures, atypical femoral fractures, and spinal fusion procedures makes it valuable in improving bone healing and reducing complications. Teriparatide also improves bone density and strength in individuals with osteogenesis imperfecta, helps prevent and treat hypocalcaemia post-thyroidectomy, and helps in the management of hypoparathyroidism. In MRONJ, teriparatide improves lesion resolution and reduces bony defects. Furthermore, it potentially prevents bone metastasis in cancer patients without stimulating tumour growth. Nevertheless, teriparatide may cause short-term side effects like nausea and long-term concerns pertaining to the risk of osteosarcoma. Recent European alliance of associations for rheumatology guidelines have highlighted teriparatide’s superior effectiveness in achieving bone mineral density thresholds and reducing fracture risks. Further clinical trials are necessary to determine optimal dosages and treatment durations of teriparatide. The off-label use of teriparatide should be considered only under the guidance of a healthcare professional when standard options are unavailable or inadequate.